The Development of a SMART Suburban Transit System for Public Transportation Service Providers and Services Users in Chiang Mai - Arunsirot, Nutreutai; Takran, Tiwawan; Pattharawongthana, Jarunee (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024DO - 10.14456/jcdr-hs.2024.27, 2024)
Public transportation plays a pivotal role in ensuring mobility for individuals who lack access to private vehicles, facilitating their seamless travel within and between urban and rural areas. Moreover, it enhances accessibility by providing low-income individuals with a means to reach essential services and opportunities, thereby promoting social equity and inclusivity. However, the public transportation system in Chiang Mai continues to face challenges in devising effective solutions to adequately meet the evolving needs of its users. This study aimed to investigate the public transportation service drivers’ and users’ opinions on current suburban public transportation services in Chiang Mai, develop a SMART Suburban Transit System for Public Transportation Service Providers and Services Users in Chiang Mai, and explore the level of user satisfaction with the implementation of the SMART Suburban Transit System. The research sample comprised 1,000 passengers and 20 drivers selected through convenient sampling. Additionally, a sample of 150 participants was recruited through purposive sampling. This included 100 regular public transportation app users, 40 drivers, and 10 staff members from Baan Tawai Transit Service Co., Ltd. All participants possessed Android-based mobile phones. Data were collected using two types of questionnaires for assessing opinions and satisfaction, as well as semi-structured interviews. The data were analyzed using descriptive statistics including mean and standard deviation. The results revealed that users’ attitudes towards suburban public transportation services in Chiang Mai had a low overall mean of 1.89. Frequency and reliability emerged as the primary concern, followed by travel time, accessibility and convenience, driver behavior, and price. Service providers expressed concerns about the proliferation of ride-hailing services such as Grab Car, which posed a significant challenge to suburban public transportation, reducing market share and revenue. The absence of government support further weakened the competitive position of suburban public transportation services. To address these challenges, a SMART Suburban Transit System was developed, comprising three components: a web-based platform for service providers, an Android-based mobile application for drivers (BTTS Application), and an Android-based mobile application for users (BaanTawai Application). After implementation, user satisfaction with the system was moderate, with a mean of 3.34 and a standard deviation of 0.33. This indicates that the system effectively addressed the concerns of users and service drivers, improving the overall experience of suburban public transportation in Chiang Mai. The study’s findings highlight the challenges faced by the public transportation system in Chiang Mai, particularly in meeting the evolving needs of users. The development and implementation of the SMART Suburban Transit System demonstrate the potential of technology-driven solutions to improve the convenience, reliability, comfort, and safety of its services. Keywords: Smart Suburban Transit System, Mobile Application, User Satisfaction